Feasibility study for slope soil stabilization by microbial induced carbonate precipitation (MICP) using indigenous bacteria isolated from cold subarctic region. - Gowthaman, S.; Iki, T.; Nakashima, K.; Ebina, S.; Kawasaki, S. (Springer Nature., 2019)
Microbial induced carbonate precipitation (MICP) is relatively an innovative soil improvement technique, learnt from the bio-mediated geochemical reactions that naturally occur in the earth surface. During the MICP, CaCO3 is metabolically precipitated in soil pores, cement the particle contacts and improves the strength and stiffness of soil. Environment temperature is one of the most key factors that determines the efficiency MICP. The purpose of this study is to investigate the feasibility of stabilizing the slope soil of cold subarctic region (Hokkaido, Japan). The implication of MICP in cold subarctic zones remains as a major challenge, as the enzymatic performance of the bacteria typically declines during lower temperatures hence insufficient formation of CaCO3 in soil matrix. Therefore, as a potential approach, this study attempted to investigate the feasibility of using the bacteria which have been adapted to native cold climatic conditions. The objectives of this paper are evaluating (1) the effect of temperature in bacterial response, and (2) the effect of grain size distribution in cementation mechanism. The observations suggest that the enzyme activity of the bacteria is negligible at and above 30 °C, whereas it is significant at relatively lower temperatures. The comparison of treated soils suggests that the fne content in slope soil increased number of particle contacts, facilitated effective packing, and promoted the effectiveness of MICP compared to that of uniformly graded sands. Finally, the technical feasibility in slope soil stabilization was well demonstrated using model solidification test. The limitations in stabilizing the slope are also discussed in detail.
Keywords: Microbial induced carbonate precipitation.; Indigenous bacteria.; Cold subarctic region.; Slope soil.; Temperature.; Grain size distribution.